PENGARUH TRANSFORMATIONAL LEADERSHIP TERHADAP COMPETITIVE ADVANTAGE MELALUI LEARNING ORGANIZATION SEBAGAI VARIABEL INTERVENING PADA PERUSAHAAN RITEL BERSKALA INTERNASIONAL DAN NASIONAL DI SURABAYA - Vilency, Virany (Business Accounting Review, 2015)
This study is aimed to know the affect of transformational leadership on the competitive advantage through learning organization as the intervening variable. The data used in this research were primary data in the form of questionnaires. This study used international and national scaled companies that engaged in retail field in Surabaya by using purposive sampling method. Data analysis method used was structural equation model (SEM) to know the relationship between the variables. The result showed that transformational leadership significantly affected the competitive advantage directly, and indirectly through intervening variable, which was learning organization.